Evaluation of the occurrence of work‐related musculoskeletal pain among anesthesiology, intensive care, and surgical nurses: An observational and descriptive study - Rypicz, Łukasz (Nurs Health Sci, 2020)
Clinical nurses can encounter musculoskeletal pain episodes stemming from regular exposure to workplace risk factors that contribute to overloads. This study aimed to evaluate the occurrence and location of work‐related musculoskeletal pain among Polish nurses. An observational and descriptive survey study was conducted among 136 nurses working in the anesthesiology, intensive care, and surgery units. An extended version of the Nordic Musculoskeletal Questionnaire was used to investigate musculoskeletal pain. Only 8% of the participating nurses experienced no musculoskeletal pain, while 85% suffered from pain in more than one location. The lower back (67%), upper back (59%), and neck (66%) were the most common pain locations. In summary, nurses experienced multiple musculoskeletal pain episodes, occurring most frequently in the spinal region (lower and upper back and neck). It is crucial to determine the real causes of musculoskeletal pain and to take appropriate preventive measures to improve workplace ergonomics.